Environmental citizen science practices in the ILTER community: Remarks from a case study at global scale - Bergami, Caterina; Campanaro, Alessandro; Davis, Cathlyn; L’Astorina, Alba; Pugnetti, Alessandra; Oggioni, Alessandro (Frontiers in Environmental Science, 2023)
In the last decades citizen science (CS) is experiencing an increasing interest as a practice in which scientists and citizens collaborate to produce new knowledge for science, society and policy. Environmental and ecological sciences are among the most active in proposing CS activities and new models for citizen participation in research. These fields necessarily include social and cultural dimensions, besides the environmental ones, to confront the complex local and global environmental challenges. This aspect is particularly evident in the International Long-Term Ecological Research (ILTER) network, where the integration of social sciences has become a recognized priority. ILTER offers a valuable landscape to explore common CS features across a wide range of different cultural and socio-ecological contexts, as well as worldviews of science-society interactions. With this purpose, in 2020 we surveyed scientists working at ILTER sites across the globe, aiming at assessing the main features of CS initiatives in which they are/were involved and the levels of participation of the volunteers. In general, the ILTER community demonstrated a good predisposition toward environmentally focused CS initiatives, with diverse scientific questions spanning from biodiversity to water quality, ecosystem services and climate change. Most of the respondents affirmed that the volunteers were involved mainly in the phase of collecting samples or recording data, but other activities including dissemination of the project conclusions, discussion and translation of the results into action were also mentioned. Volunteers were usually trained during the initiatives and acknowledged when peer-reviewed publication were produced, while data coming from the initiatives were only partially shared openly. In this paper, we discuss the main features of the CS initiatives by comparing them with the “Ten Principles of Citizen Science”, developed by the international CS community, considering in particular these main issues: (i) the scientific outcomes and societal/policy impact, (ii) the type of volunteers’ involvement, and (iii) the sharing of data and findings, the feedbacks and the acknowledgements. We conclude with remarks and suggestions for expanding design and implement CS in the ILTER community.